Optimal placement of phasor measurement unit in distribution networks considering the changes in topology - Su, Hongzhi; Wang, Chengshan; Li, Peng; Liu, Zhelin; Yu, Li; Wu, Jianzhong (Applied energy, 2019)
•A generalized integer linear programming model of the PMU placement is proposed.•Topology changes are considered to guarantee the observability with multiple topologies.•The effects of existing measurements and their relevance are covered. Distribution networks usually have a meshed structure but are operated radially to improve the operating efficiency and ensure the power supply under an emergency situation. It is of great significance to guarantee the observability of the entire system under the topology changes in operation. This paper proposes an optimal placement method of phasor measurement unit (PMU) for distribution networks. A generalized binary integer linear programming (ILP) model for PMU placement is proposed. The changes in topology are considered to guarantee the observability under any possible operation mode. The existence of zero injection nodes (ZINs), the existing measurements, and their relevance are also covered in the proposed method to reduce the installed PMU number. The objective of the ILP problem is weighted by the degree of the corresponding node to obtain a scheme with higher measurement redundancy. The correctness and effectiveness of the proposed method are verified via case studies on the IEEE 33-node test feeder, PG&E 69-node test feeder, and a medium voltage distribution network in Southern China.